The Effect of Three Rootstock Cultivars, Potassium Soil Applications and Foliar Sprays on Yield and Quality of Vitis vinifera L. cv. Ronelle in South Africa - Avenant, E.; Avenant, J.H.; Barnard, R.O. (South African Journal of Enology and Viticulture, 2017)
The early black cultivar Ronelle is the major export table grape produced in the northern summer rainfall area of South Arica.  In a rootstock trial at Roodeplaat near Pretoria, low yield, poor quality and low export mass as well as typical potassium (K) deficiency symptoms were observed for Ronelle grafted onto 110 Richter, despite K saturation percentages of 6,3% and 6,0% in the topsoil and subsoil respectively. The effect of 500 kg ha-1 and 1 000 kg ha-1 soil-applied K combined with a 0,02% foliar application of K was investigated for Ronelle grafted onto 110 R (V. rupestris x V. Berlandieri), 101-14 Mgt (Y. riparia x V. rupestris) and 143 B Mgt (v. riparia x V. vinifera). The K fertilizer treatments were applied only once, before budbreak. Three foliar sprays were applied annually, at two-week intervals, commencing at 15 cm shoot length. Results after two seasons showed that neither high levels of K fertilizer, nor K foliar sprays improved yield or quality of Ronelle on 110 R. The K content of leaves was not significantly affected by any of the K treatments. Leaf K levels of 110 R were significantly lower compared to those of 143 Mgt, but the leaf K content of all three graft combinations was above the minimum norm. Apparently there is no effective cure for established Ronelle/110 R vineyards with K deficiency problems and it is recommended that the Ronelle/110 R graft combination is not used in future.